2020
DOI: 10.1177/1947603520954510
|View full text |Cite
|
Sign up to set email alerts
|

Location Distribution of 2,087 Osteochondral Lesions of the Talus

Abstract: Objective The primary aim of this study was to evaluate the exact location distribution in patients with osteochondral lesions of the talus (OLTs) using a 9-grid scheme. The secondary aim is to match lesion location to lesion size, arthroscopic or open operation, and trauma occurrence. Methods A systematic review was performed in the databases PubMed, EMBASE, and Cochrane. Search terms consisted of “talus” and “osteochondral lesion.” Two independent reviewers evaluated search results and conducted the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 83 publications
(114 reference statements)
2
22
1
1
Order By: Relevance
“…The 9-grid scheme by Elias et al 28 and Raikin et al 19 was used and the study concluded that the majority of the lesions were located on the anterior talar dome with a higher incidence rate on the anterolateral talar dome. This finding is in contrast to the findings of a recently performed meta-analysis by van Diepen et al 7 who found that 59% of the osteochondral lesions of the talus were located on the posterior side of the talar dome with the most commonly reported anatomical location being the centromedial zone (31%). As the publication by van Diepen et al 7 consisted of mostly chronic osteochondral lesions and because of the fact that there is evidence that (antero)lateral lesions are potentially predominantly caused by traumatic events, it can be stated that the finding of the anteriorly located (O)CLs in the isolated syndesmotic injury group follows the specific evidence currently available on location distribution.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The 9-grid scheme by Elias et al 28 and Raikin et al 19 was used and the study concluded that the majority of the lesions were located on the anterior talar dome with a higher incidence rate on the anterolateral talar dome. This finding is in contrast to the findings of a recently performed meta-analysis by van Diepen et al 7 who found that 59% of the osteochondral lesions of the talus were located on the posterior side of the talar dome with the most commonly reported anatomical location being the centromedial zone (31%). As the publication by van Diepen et al 7 consisted of mostly chronic osteochondral lesions and because of the fact that there is evidence that (antero)lateral lesions are potentially predominantly caused by traumatic events, it can be stated that the finding of the anteriorly located (O)CLs in the isolated syndesmotic injury group follows the specific evidence currently available on location distribution.…”
Section: Discussioncontrasting
confidence: 99%
“…Our secondary hypothesis is that lesion size is heterogeneous and that most lesions are located in the anterolateral talar dome which is known to be a more common location for post-traumatic (O)CLs of the ankle. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic joint debridement and microfracture are indicated for the management of limited (no more than 15 mm in diameter and 8 mm in depth) OLTs [ 21 , 22 ]. OLTs are commonly encountered in CLAI patients undergoing surgery and are mostly located over the centromedial portion and the anterolateral portion of the talus [ 23 , 24 ]. It is more likely that OLTs of the medial portion of the talus are present in patients with long-standing CLAI [ 25 ] and rotational instability of the ankle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the normal model, the talus cartilage was divided into 9 regions by the nine-grid partition method. Studies have shown that area 4 is the most common area for talus cartilage injuries [13,14]. In this study, defects in the cartilage and subchondral bone in region 4 of the talus were simulated.…”
Section: Construction Of the Working Condition Modelmentioning
confidence: 99%